Remote renewable energy laboratory: Green Electric Energy Park (GEEP) - Mohammadi, N.; Murray, Iain; Hsiung, G. (2017)
Distributed teaching of engineering subjects requires the accessibility of equipment and devices over the Internet The authors have developed an effective environment for remote renewable engineering laboratories and distance learning. This paper covers the background, methods, evaluation and analysis of remote laboratory model designed and implemented to consolidate data, video and audio feeds gathered from Curtin University's Green Electric Energy Park (GEEP) facility into a VMWare virtual machine, accessible through NDG's NETLAB+ platform. The model was designed with the desire of reducing the bandwidth overheads when attempting to access particular feeds and stable connectivity in a secure manner to provide Curtin international partner students with the same laboratory environment as local students.